Evaluation of the bristle end‐rounding patterns of children's toothbrushes using scanning electron microscopy and stereomicroscopy. Issue 2 (17th September 2015) - Lee, H‐S; Jung, H‐I; Kang, S‐M; Kim, H‐E; Kim, B‐I
Abstract: Objectives: The aim of this study was to evaluate the proportions of end‐rounded bristles via observations of the end patterns of various children's toothbrushes with scanning electron microscopy (SEM) and stereomicroscopy. Methods: Ten different brands of children's toothbrushes were chosen, and tufts from each toothbrush were used. The prepared bristle specimens were observed on SEM and stereomicroscopic images and classified as acceptable (A1–A3) and non‐acceptable (N1–N5) according to the modified classification. Then, the proportions of end‐rounded bristles were calculated. Results: Analyses of the 10 toothbrushes revealed that the proportions of acceptable end‐rounded bristles ranged from 1.4% to 20.2% on SEM and from 0.0% to 18.0% on stereomicroscopic examinations. Additionally, some toothbrushes had labels that indicated bristle end‐rounding, but the proportions of end‐rounded bristles were low. Conclusions: The types and percentages of bristle ends of children's toothbrushes marketed in Korea were various, but the amount of acceptable end‐rounded bristles was low. The result, that even toothbrushes labelled as end‐rounded had potential to harm oral tissue, demonstrates that quality control for rounding bristle ends as well as the labelling for end‐rounded bristles is needed.